The Reception of Aristotle's Metaphysics in Avicenna's Kitāb al-Šifā' : A Milestone of Western Metaphysical Thought - Bertolacci, Amos, (Brill Book Archive Part 1, ISBN: 9789004472495., 2006)
This volume deals with the reception of Aristotle's Metaphysic s in the masterpiece on metaphysics by Avicenna (Ibn Sīnā, d. 1037 C.E.), one of the major exponents of Arabic philosophy: the Ilāhiyyāt (Science of Divine Things) of the Kitāb al-Šifā' ( Book of the Cure ), known in the Latin Middle Ages as Liber de Philosophia Prima sive Scientia Divina. The first part of the book (on the Arabic translations of the Metaphysics , al-Kindī and al-Fārābī) introduces the discussion of Avicenna's reshaping of the epistemological profile of the Metaphysics in Part II (his account of the subject-matter, structure, method and role of metaphysics in the system of sciences) and the recasting of its contents in Part III. The present volume provides the first systematic comparison of the Ilāhiyyāt with the Metaphysics and a comprehensive account of this latter's transmission in pre-Avicennian Greek and Arabic philosophy.